An enhanced spray and wait DTN routing protocol based on node mobility and maximum number of replications. (1st January 2014) - Henmi, Kenta; Koyama, Akio
Spray and wait protocol, which is a typical routing protocol in delay/disruption/disconnection tolerant network (DTN), sets a maximum number of replications per message for restricting a number of replications. However, it is difficult to set a maximum number of appropriate replications in advance. Moreover, there is possibility to replicate to nodes that do not contribute to the data arrival, because appropriate replicated nodes are not selected. In this paper, we propose a routing method to dynamically set the maximum number of appropriate replications depending on network states and to select appropriate relay nodes. We verified by simulation that the proposed method has high packet delivery rate compared with conventional methods.